ANALISIS STRUKTURAL, NILAI MORAL DAN NILAI SOSIAL DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - Sekar Ayutya (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
Novel is a literary work that is built in totality through various intrinsic and extrinsic elements that are interrelated and have an artistic character. Based on this, the researcher is interested in studying the structural elements that build literary works, moral values and social values contained in a novel entitled Guru Aini by Andrea Hirata. The type of approach used in this research is a qualitative approach with descriptive methods. This research is a library research using data sources in the form of written documents from a novel entitled Guru Aini by Andrea Hirata. The results in this study are as follows; (1) The theme of education and the struggle to achieve a dream. (2) The flow used is the forward and backward flow. (3) There are two types of characters in this novel. As the main characters, namely Guru Desi and Aini. Meanwhile, as additional figures, namely Debut Awaludin, Pak Tabah, and Laili. (4) The setting used is in the form of place setting, time setting, and social setting. (5) The point of view used is the point of view of the third person with the omniscient "he" technique. (6) The mandate contained in the idealism of a teacher, an unyielding attitude, and devotion to both parents. The moral values contained in the novel Guru Aini by Andrea Hirata include the value of human relations with God, human relations with oneself, human relations with others, and human relations with the environment. While the social values contained include the values of love, responsibility, and life harmony.